Etika Guru PAK bagi Sikap Etis Politik Identitas Dalam Mereduksi Superioritas - Wasari, Desi; Triposa, Reni; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2022)
This study aims to describe the ethical paradigm and the role of the Christian Religious Education teacher profession in addressing identity politics with ethical actions in an effort to reduce superiority. The ethical attitude and professionalism of Christian Religious Education teachers play an important role in educating and instilling Christian values in students. So that it can reduce the superiority in identity politics that often occurs in community groups. Identity politics occurs when minority identity groups are excluded from majority identity groups. Therefore, through this research, the author conveys that through the ethical paradigm and the teaching profession of Christian Religious Education, it will actually help efforts in reducing the superiority of identity politics. Using a descriptive qualitative method with a literature study approach, it can be concluded that the indicators of the paradigm and nature of ethics, as well as the role of the Christian Religious Education teacher presented in this study can assist the reader in understanding how the ethics and profession of Christian Religious Education teachers for the ethical attitude of identity politics in attempts to reduce superiority.AbstrakPenelitian ini bertujuan untuk mendeskripsikan tentang paradigma etika dan peranan profesi guru Pendidikan Agama Kristen dalam menyikapi politik identitas dengan tindakan etis dalam upaya mereduksi superioritas. Sikap etis dan keprofesinalitas guru Pendidikan Agama Kristen sangat memegang peranan penting dalam mendidik dan menanamkan nilai-nilai kekristenan kepada peserta didik. Sehingga dapat mengurangi superioritas dalam politik identitas yang sering terjadi dalam kelompok masyarakat. Politik identitas terjadi ketika kelompok identitas minoritas dikesampingkan dari kelompok identitas mayoritas. Oleh karena itu, melalui penelitian ini penulis menyampaikan bahwa melalui paradigma etika yang etis dan profesi guru Pendidikan Agama Kristen maka sejatinya akan membantu upaya dalam mereduksi superioritas politik identitas. Menggunakan metode kualitatif deskriptif dengan pendekatan studi literatur maka dapat disimpulkan bahwa Indikator-indikator paradigma dan hakikat etika, juga peran guru Pendidikan Agama Kristen yang dikemukakan dalam penelitian ini dapat membantu pembaca dalam memahami bagaimana etika dan profesi guru Pendidikan Agama Kristen bagi sikap etis politik identitas dalam upaya mereduksi superioritas.